POINT OF SALE SYSTEM A BILLING SYSTEM INFRASTRUCTURE. - G., SIVAKUMAR; P., RAVIKUMAR; J. S., VIMALI; KUMARI, G. ROSLINE NESA; MARUTHUPERUMAL, S. (Turkish Journal of Physiotherapy Rehabilitation, 2021)
The paper is about the point of sale (POS) system Implemented in Embedded Systems. Point of sale is the payment scenario, when a customer performs payment to the merchant whenever a product is bought. After the payment, the merchant will issue a payment receipt or an invoice regarding the payment, these payment receipts are printed or sent electronically. To calculate the amount to be paid by the customer for what he/she purchased, the merchant uses various devices such as cash registers, weighing scales and to control all these devices a microcontroller is used in hardware. The microcontroller processes all the input data given to it and output's the processed data to the required output console. To process those data, a programmer should give a proper algorithm to the microcontroller through any programming language which is accepted by the microcontroller. Ex. C, Python etc. In this paper a proper algorithm is given to the microcontroller through C programming language, in order to solve the point of sale problem. The problem can be solved by getting data input to the microcontroller through various input devices such as weighing scales, Keyboards and output as a bill to the billing machine. This system is an integrated weighing point of sale (POS) system, such that the weighing scale measured weight for each item is directly displayed in the output screen. POS system enables quick product return processes. When a customer cancels a sale, the merchant can process it through POS system with just a couple of clicks. The stock number of an item that was reduced automatically increases again once a purchase has been cancelled. The Accounting details of a grocery store can be stored in well organized manner either it may be the tax amount, total revenue collected by the store or the detailed item wise stock report using a PC/mobile application.